ASSESSMENT OF DIFFERENT GENOTYPES OF TABLE BEET FOR PRODUCTIVITY AND STORABILITY - B. M. Amirov; Z. S. Amirova; U. A. Manabaeva; K. R. Zhasybaeva (Овощи России, 2017)
The experiments were performed during the two successive seasons of 2015-2016 and 2016-2017 at the Kazakh Research Institute of Potato and Vegetable Growing, Almaty Region, Kazakhstan. The experiment was aimed to study the efficiency of 117 different beetroot accessions for productivity and storability. To study the storability, 20 beetroot roots without any external sings of diseases were taken in two replications from each variety accession and left to be stored. The wet fresh weight of beetroots placed into storage varied from 132 g to 320 g depending on the shape and the size of roots. Beetroots were stored in polypropylene bags, which were placed on barred shelves 30-35 cm high. The storing temperature in autumn and spring period of time fluctuated from 3-5o to 6-8°, but in winter period it was 1-2°. The observed results showed that the gross yield of beetroot accessions ranged from 25.0 to 105.4 t/ha, marketable yield – 16.7 to 74.9 t/ha, marketability – 33.8 to 97.2%. Storability of beet roots mostly depended on accession genotype with different natural decrease of weight and root rot diseases. Natural decrease of weight varied from 0.0 to 12.3%, total losses from root diseases were from 0.0 to 90.0%. The analysis carried out showed that the link between yield capacity and storage characteristics was weak, R= -0,042-0,144. The correlation between storability and root rot was R = -0,516-0,644, that was stronger than it was in natural decrease of weight, R = -0.115.